Improving the approaches to the implementation and stages of monitoring the quality of construction - Nikohosyan, N.; Litvinenko, L. (Ways to Improve Construction Efficiency, 2019)
The experience of implementation of internal monitoring of the construction quality system based on the process approach is considered. This approach involves highlighting and evaluating the quality of business processes of an individual enterprise and other participants in the construction process, optimizing the flow of their information, logistical, financial and labor resources, developing methods and programs aimed at improving the quality of construction products. It is argued that in order to build a quality system of a construction object, it is necessary not only to have a holistic project for the implementation of the investment-construction process and specifically related to the implementation of design decisions procedures that are part of the strategic planning system for the construction of the object, but also to consider the role, functions and the relationship of each of the participants in the investment and construction process. In order to check the quality system of construction, it is proposed to describe the basic and auxiliary construction processes and periodic self and external control of their quality, that is, to check the conformity of works and construction materials with design decisions, requirements of state norms and technical conditions, complexity and compliance with the requirements of technology and organization of construction, input control, geodetic control, etc. Monitoring, which integrates the observation, collection, analysis, processing of information on the state of the object for the purpose of evaluation, forecasting and dissemination of information, will allow to make informed decisions both on the current optimization or adjustment of parameters of the construction process, and on the strategy of further development of the construction enterprise. , optimization of production, financial and investment activity. Monitoring stages have been identified. The first step in the research of the construction quality monitoring system is to determine the information flows between the construction participants, their functional responsibilities and responsibilities. The second stage is the development of goals and planning of the monitoring process, which includes the following procedures: Defining strategic goals and planning; Choice of research methods and methods; Monitoring process; Generalization of data, identification of reasons for deviation of indicators and adjustment of quality of construction process.